Dynamics of coupled structures. Volume 4 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Allen, Matt (Mechanical engineer); Mayes, R.; Rixen, Daniel (Springer, 2017)
Dynamics of Coupled Structures, Volume 4: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the fourth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of the Dynamics of Coupled Structures, including papers on: Experimental Nonlinear Dynamics Joints, Friction & Damping Nonlinear Substructuring Transfer Path Analysis and Source Characterization Analytical Substructuring & Numerical Reduction Techniques Real Time Substructuring Assembling & Decoupling Substructures & Boundary Conditions.
Keywords: Modal analysis -- Congresses.; Structural dynamics -- Congresses.; elektronické knihy; electronic books